2023
DOI: 10.1007/s10461-022-03963-4
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Symptoms of Mental Health Disorders Among People with HIV Initiating HIV Care in Cameroon

Abstract: Little is known about the coping strategies used among people with HIV (PWH), especially in sub-Saharan Africa, and the extent to which adaptive or maladaptive coping strategies are associated with symptoms of mental health disorders. We interviewed 426 PWH initiating HIV care in Cameroon and reported the prevalence of adaptive and maladaptive coping strategies, overall and by presence of symptoms of depression, anxiety, and PTSD. Log binominal regression was used to estimate the association between each type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…Los resultados de este estudio revelaron una prevalencia del TEPT del 42%. Por otro lado, en el segundo estudio se examinó a un grupo más amplio de 426 pacientes utilizando la herramienta de Verificación de Eventos de la Vida para el DSM-5 (LEC-5) según el trabajo de Parcesepe et al, (2023). En este caso, se encontró una prevalencia significativamente más alta, alcanzando un 86% en relación con el TEPT.…”
Section: Q4unclassified
“…Los resultados de este estudio revelaron una prevalencia del TEPT del 42%. Por otro lado, en el segundo estudio se examinó a un grupo más amplio de 426 pacientes utilizando la herramienta de Verificación de Eventos de la Vida para el DSM-5 (LEC-5) según el trabajo de Parcesepe et al, (2023). En este caso, se encontró una prevalencia significativamente más alta, alcanzando un 86% en relación con el TEPT.…”
Section: Q4unclassified
“…One study among PLWH in the US showed that PLWH who report higher levels of negative coping strategies, such as self-blame, tend to have higher levels of alcohol use, while those who use positive coping strategies, such as seeking social support, exhibit lower levels of alcohol use [ 29 ]. The use of avoidance coping strategies, such as denial and substance use, has been associated with higher symptoms of depression and anxiety among PLWH initiating HIV care in Cameroon [ 30 ]. Additionally, the relationship between coping strategies and HRQOL has also been found to vary by gender among PLWH, with women reporting lower HRQOL scores and using negative coping strategies more frequently than men [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…These strategies are crucial for managing symptoms, improving mental health outcomes, and enhancing overall well-being. Research has highlighted the significance of positive coping mechanisms, such as social support and personal resilience, in mitigating the impact of stress and promoting mental health among adolescents facing various adversities (Ismail et al, 2021;Parcesepe et al, 2023).…”
Section: Introductionmentioning
confidence: 99%